Avaliação do potencial de aproveitamento de resíduos da extração de óleo de buriti para produção de pós ricos em fibra alimentar com compostos antioxidantes associados - Laís Maia Resende (2016)
Buriti is a fruit native to Brazil, whose oil is used in cosmetics. The extraction can be done by a handmade process or by an industrial process. The handmade bran is the residue generated when extracting oil from the whole fruit. In industry, extraction is made by pressing the pulp, this procedure generates some residues such as shells, endocarp, seeds and bran. Buriti is a fruit rich in dietary fiber and antioxidants. These products are beneficial to health and can be used by the industry to add value and improve the properties of processed foods. The objective of this study was to investigate whether the residue generated in the processing of buriti are good raw materials for the preparation of high dietary fiber powders, associated with antioxidant compounds. Fruits were collected and characterized. Two methods were used to extract the oil, a handmade process was used to extract oil from the whole fruit, and the solvent extraction method was used to simulate an industrial procedure for the pulp. From the residues generated by the aforementioned processes, six potential high dietary fiber powders were produced, using bleached shells, unbleached shells, bleached endocarp, unbleached endocarp, handmade bran and bran. The powders were subjected to the following analysis: colorimetry; proximate analysis; insoluble dietary fiber and soluble dietary fiber content; determination of neutral sugars; antioxidant activity; extractable and nonextractable polyphenol contents; anthocyanins content; carotenoids content; and technological properties. All the powders showed similar features found in commercial products: typical particle size, clear color, moisture lower than 9%, low content of lipids, and total dietary fiber content higher than 50%. The powders produced from the shells and bran showed the best antioxidant potential, intermediate to similar products described in the literature. The handmade bran showed intermediate antioxidant potential and the endocarp showed the lowest antioxidant potential. All powders showed high nonextractable polyphenols content. These results demonstrate that the antioxidant activity is underestimated. Bleaching appears to preserve extractable polyphenols content, but not carotenoids and nonextractable polyphenols content, being also sufficient to lighten the powders. The buriti residue has the potential to be utilized in the preparation of high dietary fiber powders associated with antioxidant compounds.